POSISI BAWASLU SEBAGAI PIHAK KETIGA DALAM SENGKETA PEMILU - Hariadi; Ahmad Rustan; Irwansyah (Jurnal Hukum Lex Generalis, 2024)
This study examines the position of the Election Supervisory Agency (Bawaslu) as a third party in election disputes in Indonesia. Bawaslu plays an important role in the supervision and resolution of election disputes, including in handling administrative violations and election crimes. Research shows that Bawaslu faces challenges in harmonizing authority with other institutions, such as the KPU and the Constitutional Court, as well as in increasing public participation in election supervision. Through a normative juridical approach, this study highlights the need for regulatory clarity and collaboration between institutions to realize democratic and transparent elections.